Shariah review of Islamic profit rate swap strategies in Islamic financial institutions : the case of Malaysia - Agha, Syed Ehsanullah (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2015)
“Nothing ventured, nothing gained” is the first principle of investment. The possibility of an adverse outcome is an essential part of business activities. This uncertainty about future outcomes is defined as risk. The broad perspective on risk and its management is embodied in the essential objectives of Shari'ah, which is wealth protection. However, in the light of the Shari'ah legal maxim that states 'al-ghurm Bi al-ghunm' (liability accompanies gain) and 'al-kharaj Bi al-Daman' (benefit goes with liability) risk cannot be isolated from economic affairs. The legitimacy of revenue generation requires that it has to be created based on real economic activities that involve real business risk and liability. On the other hand, exposing to excessive risk not only hurdles investment, but also deters economic growth, which might be against the maqasid al-Shari'ah (objectives of Shari'ah). As Islamic finance industry grows 15 to 20 percent annually, the need of hedging tools to mitigate certain risks in a volatile market increases. For instance, with a rapidly emerging market of Sukuk, both investors and issuers are exposed to currency fluctuation risk. Similarly, in the case of Islamic REITS, if the fund is invested in overseas properties. Islamic Profit Rate Swap (IPRS) is a contract designed as a hedging mechanism to minimize market participants' exposure to the risk of inflation and rate of return. By nature Swap products are derivatives which violate Shari'ah principles. According to Sami Al- Suwailem 97.30% of derivatives products are being used for speculation. This research aims to review from Shariah perspective the legality of the structure and mechanism of Islamic profit rate swap as currently offered by many Islamic financial institutions in Malaysia. Specifically the paper highlights the Shariah parameters and guidelines in structuring IPRS. It is observed that IPRS products may involve the following Shariah Issues: Combination of Several Contracts, Use of the same commodity for various Murabaha transitions, Organized Twarruq, Premature Termination and Mark to Market. Finally, an improved new structure of IPRS is proposed to reduce operational cost and Shari'ah non-complaint risk for Islamic financial institutions.